Assessing the Effect of Sediment Deposits on the Performance of Residential Heating Radiators: An Experimental Investigation - Mahboobeh Ebrahimi; Mousa Farhadi; Alireza Rezaniakolaei (Journal of Heat and Mass Transfer Research)
In this investigation, we present pioneering findings on the detrimental effects of sediment deposits on the thermal and hydraulic performance of residential heating radiators through a novel experimental framework. Our approach, through the systematic introduction of particulate matter into the water circuit, quantifies the real-world impact of sediment accumulation. This methodology fills a significant void in literature with validated experimental data and establishes a method for assessing radiator performance under fouled conditions, adhering to ISO 3148 standards. The experimental results underscore a significant efficiency downturn: sediment presence increased pressure drop by up to 10.5% and reduced surface temperature by as much as 13%. Notably, heat output initially saw a slight increase, only to decrease by up to 28.5% over time, with these effects amplifying at higher inlet temperatures. These findings underscore the urgent need for tailored maintenance strategies to combat sediment-related degradation, offering invaluable insights for the design, maintenance, and optimization of heating systems beneficial to both industry stakeholders and end-users.